Case Report: Persistent Pulmonary Hypertension of the Newborn and Narrowing of the Ductus Arteriosus After Topical Use of Non-Steroidal Anti-Inflammatory During Pregnancy - Le Duc, Kévin; Gilliot, Sixtine; Baudelet, Jean Benoit; Mur, Sébastien; Boukhris, Mohamed Riadh; Domanski, Olivia; Odou, Pascal; Storme, Laurent (Frontiers in Pharmacology, 2021)
Background: The use of non-steroidal anti-inflammatory drugs (NSAIDs) during the third trimester of pregnancy can cause premature constriction of the ductus arteriosus. This report describes a case of in utero narrowing of the ductus arteriosus (DA) diagnosed postnatally in a baby with Persistent Pulmonary Hypertension of the Newborn (PPHN), after maternal use of Diclofenac-Epolamine 140 mg patch during the second and third trimester. Case Presentation: A fetal ultrasounds revealed an enlarged hypertrophic right ventricle at 32 weeks of gestation. Detailed questioning of the mother highlighted that topical Diclofenac (FLECTOR ®) had been used at 26 and at 31 weeks of gestation. An echocardiography performed 8 hours postnatally showed supra-systemic pulmonary hypertension, a restrictive ductus arteriosus and a dilated right ventricle. The newborn was treated by inhaled nitric oxide and oral Sildenafil and was discharged from hospital on day 24. He had a complete normalization of his pulmonary vascular resistance on day 48. Conclusions: This case illustrates the potential fetal and neonatal complications associated with maternal topical Diclofenac medication during pregnancy resulting in antenatal closure of the DA.